1D seismic site response analysis for a soil deposit at Baoding city. Issue 1 (June 2020) - Jia, Qijun; Wang, Duguo; Zhai, Fenlou; Liu, Xiaoyu
Abstract: Based on 1D equivalent linear method, the effect of a soil deposit at Baoding city on wave propagation was analysized. Firstly, probabilistic seismic hazard analysis (PSHA) was performed, and the peak accelartion and response spectrum of outcrop with exposure rate over 63%, 10% and 2% in 50 years are obtained; secondly, the artificial earthquake ground motions used as input motion of soil deposit were synthesized; lastly, 1D equivalent linear analysis was performed to evaluate the effect of soil deposit on wave propagation. Results show that soil deposit has a great influence on wave propagation. The intensity of input motion also plays an important role on the properities of seismic ground motion.